Pancreaticopleural Fistula: Navigating the Enigma of an Elusive Diagnosis - Karthik Volety; Purvil Joshi (University Library System, University of Pittsburgh, 2023)
BACKGROUND: Pancreaticopleural Fistula is a Rare Complication of Acute and Chronic Pancreatitis. This Usually Presents With Chest Symptoms Due to Pleural Effusion, Pleural Pseudocyst, or Mediastinal Pseudocyst. Diagnosis Requires a High Index of Clinical Suspicion in Patients Who Develop Alcohol-induced Pancreatitis and Present With Pleural Effusion Which is Recurrent or Persistent. Analysis of Pleural Fluid for Raised Amylase Will Confirm the Diagnosis and Investigations Like Ct. The Rarity of Pancreaticopleural Fistulas, Especially Without the Context of Chronic Pancreatitis, Makes This Case Noteworthy. The Presence of Pleural Effusion in the Absence of Lung Disease Prompted Thorough Investigation, Leading to the Identification of an Unusual Etiology. THE CASE: A 35-year-old Alcoholic Male Presented to Emergency Room With 4-day History of Breathlessness Which Was Sudden Onset, Gradually Progressing to Grade-3 Dyspnea on NYHA Scale, Associated With Dry Cough. Hospitalization and Chest Radiograph1 Revealed Gross Right Side Pleural Effusion. Emergency thoracentesis and Intercostal Drainage Tube Placement were done and Patient Was Referred to Pulmonology Department. On further Evaluation, Patient Also Complained of Mild Persistent Left Upper Quadrant Abdominal Pain for More Than 6 Months Which Was Relieved on Medication Hence, Ignoring the Complaint. Thoracentesis Procedure Yielded 1.5l Amylase-rich Fluid in the Pleural Space. The Patient Was Then Referred to Surgical Department for Further Evaluation. Usg Abdomen Was Inconclusive. Lab Reports Revealed Mildly Elevated Pancreatic Enzymes. contrast- Enhanced Computed Tomography (Ct) Scan of the Abdomen and Chest Revealed a Dilated Main Pancreatic Duct and Multiple Direct Communication Between the Pancreatic Duct(see Figures 1) and the Right Pleural Space, Leading to the Formation of Massive Pleural Effusion and Complete Collapse of Right Lung. Rest of the Pancreas Appeared Normal With No Evidence of Calcification. After a Thorough Clinical Evaluation, Laboratory Investigations, and Imaging Studies, the Patient Was Diagnosed With a Pancreaticopleural Fistula. The Patient Was Managed Through a Multidisciplinary Approach Involving Gastroenterology, radiology, and General Surgery Teams. Initial Management Included Aggressive Medical Treatment With Bowel Rest, Total Parenteral Nutrition, Antibiotics and Administration of Proton Pump Inhibitors. The Patient Showed Gradual Improvement Post-drainage, With a Significant Decrease in Pleural Effusion Volume and Resolution of Dyspnea. Follow-up With CT scan Was Advised. The patient Was Subsequently Monitored Continuously With Dietary Recommendations. CONCLUSION: the Chosen Case is Significant Due to Its Diagnostic Intricacies and the Necessity for Collaboration Among Various Medical Specialties. The Management of Pancreaticopleural Fistulas Requires a Tailored Approach. This Case Underscores the Importance of Early Diagnosis, Meticulous Evaluation, and Timely Intervention in Achieving Successful Outcomes for Patients. In conclusion,by Sharing This Case, I Aim to Contribute to the Understanding of This Rare Condition and Emphasize the Significance of Timely Diagnosis and Appropriate Management Strategies.